Strategic policymaking and the German aid programme in the MENA region since the Arab uprisings - Mark Furness (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
Germany's official aid to Middle Eastern and North African (MENA) countries has more than doubled since 2011, ostensibly to support their responses to development challenges and humanitarian crises following the Arab uprisings. But the dramatic increases in aid have not been accompanied by a public strategy that sets out Germany's objectives in the region, and the role of aid in conjunction with other policy tools in achieving them. Furthermore, a closer look at the figures reveals that most of the increased aid has been spent in just two areas: humanitarian aid in response to the Syrian crisis; and soft loans to Morocco for investing in renewable energy production. This raises some interesting questions for observers of German development cooperation. First, what strategic objectives does the German government have for its MENA aid, and have these objectives changed in response to the Arab uprisings? Second, does the practice of Germany's aid spending actually address development and humanitarian challenges in the MENA region? And third, why has the German government not produced a clear strategy for its aid, given the political salience of the Arab uprisings and their aftermath? In order to address these questions, this paper develops some key insights from the historical institutionalist and aid effectiveness literature that explain strategic policymaking in complex decision-making systems. Two propositions are discussed: first, that Germany's aid and foreign policy system has not been able to produce a clear strategy due to political differences and bureaucratic inertia; and second that the priorities that have been defined tend to favour German and European security interests rather than the development and humanitarian priorities of the region. An examination of the policy and practice dimensions reveals that, while efforts have been made to set priorities for development and humanitarian cooperation in response to the Arab uprisings, Germany's MENA aid programme shows signs of policy incoherence and fragmentation. This is unlikely to change in the absence of a “whole-of-government” strategy for Germany's engagement in the MENA. Furthermore, while there is little evidence of purposeful securitisation of aid, short-term stability has been privileged over support for unpredictable political change. A whole-of-government strategy based on the Sustainable Development Goals would balance German interests with the MENA region's development priorities, and thus iron out the most problematic incoherencies.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik